Symmetry and Node Focused Visualization of Large Trees - Etemad, Katayoon; Carpendale, Sheelagh (2010)
In this paper, we take a different approach to visualizing very large trees. To facilitate presentation and exploration of massive hierarchical datasets such as linguistic and genealogical hierarchies, our approach considers drawing layouts of tree-cuts as a function of a node-of-interest or NOI, and uses interaction to support rapid access to the entire tree. Instead of emphasizing overall tree structure, our layout is designed to make the most space available for the node-of-interest and its immediate ancestors and descendants. Inspired from Persian floral patterns, we describe the development of ShamsehTree and PaisleyTree, showing how the use of symmetry can provide new structures for tree layouts.